(3GdeYLRs - (3GdMSjf Hf GdbGSe Hf Ydj GdYjGfj, GdegOj dOjf Gddg,J (B404 (3g` s
(3ChdgG (B:s
(3HGH GdQO Ydi ef LMO Gddg , hbGd HbOe GdghGA hZjQg ef GdGTjGA bGd GdegOi s
(3BNQgG (B:s
(3hGdaYd gh GdKGdK GdeLYhd GdeJhSW Hjf GdbGHd hGdebHhd Je cJGH GdJfGgi hGdfLOjO ef cdGe GdEeGe GdegOi hgh BNQ cJGH GdeYLR , hMSHi Gddg s
(3jTJed Ydi (B: (3HGH GdQO Ydi ef LMO Gddgs
(3hHGH GdOdGdI Ydi MOK GdCLSGes
(3hHGH GdQO Ydi YHOI GdfLhe hZjQge ef aQbs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B252s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdESdGejs